Oscillation criteria of second order nonlinear neutral differential equations - Soliman, A. A.; Sallam, R. A.; Hassan, Ahmed Mohamed (International Journal of Applied Mathematical Research, 2012)
This paper is concerned with the oscillation of second-order nonlinear neu-tral dierential equations of the form[r(t)[(x(t) + p(t)x((t)))']'+ f(t; x( (t))) = 0;by using a generalized Riccati's technique and integral averaging technique, weestablish new oscillation results which handle some cases not covered by knowncriteria.